Effects of low‐frequency magnetic field on solubility, structural and functional properties of soy 11S globulin - Kang, Zhuang‐Li; Yao, Peng‐Lei; Xie, Jing‐jie; Li, Yan‐ping; Ma, Han‐Jun (Journal of the science of food and agriculture, 2024)
BACKGROUND Soy 11S globulin has high thermal stability, limiting its application in the production of low‐temperature gel foods. In this study, the low‐frequency magnetic field (LF‐MF, 5 mT) treatment (time, 30, 60, 90, and 120 min) was used to improve the solubility, conformation, physicochemical properties, surface characteristics, and gel properties of soy 11S globulin. RESULTS Compared with the native soy 11S globulin, the sulfhydryl content, emulsifying capacity, gel strength, water‐holding capacity, and absolute zeta potential values significantly increased (P < 0.05) after LF‐MF treatment. The LF‐MF treatment induced the unfolding of the protein structure and the fracture of disulfide bonds. The variations in solubility, foaming properties, viscosity, surface hydrophobicity, and rheological properties were closely related to the conformational changes of soy 11S globulin, with the optimum LF‐MF modification time being 90 min. CONCLUSION LF‐MF treatment is an effective method to improve various functional properties of native soy 11S globulin, and this study provides a reference for the development of plant‐based proteins in the food industry. © 2024 Society of Chemical Industry.